Implementation of The Critical Path Method for Project Scheduling Using Python (Case Study: Construction of The Official Residence for The Commander and Deputy Commander of Company C, Morut Pioneer Battalion, Central Sulawesi Regional Police) - Grace C.C. Lohonauman; Steenie E. Wallah; Grace Y. Malingkas (Jurnal Sosial Teknologi, 2026)
Construction project management quality is the primary goal of every project executor. The Critical Path Method (CPM) enables efficient project scheduling by identifying critical activities and optimizing work sequences. This study aims to schedule the construction of the official residence for the Commander and Deputy Commander of Company C, Morut Pioneer Battalion, Central Sulawesi Regional Police, using CPM integrated with Python programming. Data were collected from project schedule documents comprising 28 activities with an initial planned duration of 180 days. Using CPM analysis with Python's NetworkX library, forward and backward pass calculations were performed to determine ES, EF, LS, LF, and total float values for each activity. The results show that the project duration can be optimized from 180 days to 127 days, achieving a time saving of 53 days (29.44%). Activities with a total float value of zero constitute the critical path, while non-critical activities retain scheduling flexibility. This study demonstrates that CPM integrated with Python effectively supports project scheduling decisions, resource allocation, and timeline control in construction project management.